Analisa Bibliometric; Peran Autophagy Dalam Patofisiology Stroke Ischemic - Husnur Husnur; Erna Rochmawati (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Ischemic stroke is a leading cause of long-term disability and mortality worldwide, posing a significant health burden. Standard therapies, such as intravenous thrombolysis and mechanical thrombectomy, are limited by a narrow therapeutic window, leaving many patients without optimal care. Autophagy, a cellular degradation and recycling process, has been increasingly linked to ischemic stroke pathophysiology. Controlled activation of autophagy can confer neuroprotective effects, while dysregulation may exacerbate neuronal injury. This study aims to map global research trends, thematic focus, and knowledge gaps related to autophagy in ischemic stroke, and to explore its implications for neurological nursing practice. A bibliometric analysis was conducted using publications indexed in Scopus. Quantitative indicators included publication counts, citation analysis, keyword co-occurrence, and international collaboration networks, visualized using bibliometric software. A total of 737 articles were analyzed, showing a significant increase in publications since 2016. China was the leading contributor, followed by the United States. Research was dominated by the fields of Biochemistry, Genetics, and Molecular Biology, as well as Neuroscience. Co-occurrence analysis identified autophagy as a central node closely associated with neuroprotection and ischemia via key molecular pathways such as AMPK and PI3K/Akt/mTOR. Autophagy plays a critical role in the pathophysiology of ischemic stroke and represents a potential therapeutic target. These findings provide a scientific basis for neurological nurses to develop mechanism-based interventions that support patient recovery and enhance the quality of nursing care. Keywords: Autophagy, Stroke ischemic, Bibliometric.  ABSTRAK Stroke iskemik merupakan penyebab utama kecacatan jangka panjang dan kematian di dunia, dengan beban kesehatan yang signifikan. Terapi standar, seperti trombolisis intravena dan trombektomi mekanik, terbatas oleh jendela waktu terapi sehingga banyak pasien tidak memperoleh penanganan optimal. Autofagi, proses degradasi dan daur ulang seluler, semakin dikaitkan dengan patofisiologi stroke iskemik. Aktivasi autofagi yang terkontrol dapat memberikan efek neuroprotektif, namun disregulasi berpotensi memperburuk cedera neuron. Penelitian ini bertujuan untuk memetakan tren penelitian global, fokus tematik, dan kesenjangan pengetahuan terkait autofagi pada stroke iskemik, serta implikasinya bagi praktik keperawatan neurologi. Analisis bibliometrik dilakukan terhadap publikasi dari Scopus. dengan indikator jumlah publikasi, sitasi, ko-okurensi kata kunci, dan jaringan kolaborasi internasional menggunakan perangkat lunak visualisasi bibliometrik. Sebanyak 737 artikel dianalisis, menunjukkan peningkatan publikasi signifikan sejak 2016. China menjadi kontributor utama, diikuti Amerika Serikat. Bidang Biochemistry, Genetics, and Molecular Biology serta Neuroscience mendominasi penelitian. Analisis ko-okurensi mengidentifikasi autofagi sebagai node sentral yang berkaitan erat dengan neuroprotection dan ischemia melalui jalur molekuler seperti AMPK dan PI3K/Akt/mTOR. Autofagi berperan penting dalam patofisiologi stroke iskemik dan memiliki potensi sebagai target terapeutik. Temuan ini menjadi dasar ilmiah bagi perawat neurologi untuk mengembangkan intervensi berbasis mekanisme seluler, mendukung pemulihan pasien, dan meningkatkan kualitas asuhan keperawatan. Kata Kunci: Autophagy, Iskemik Stroke, Bibliometrik.